2002
DOI: 10.1046/j.1365-2788.2002.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the assessment and treatment of anger and aggression in offenders with intellectual disability

Abstract: Rates of aggression amongst people with intellectual disability (ID) have been found to be high in studies conducted on several continents across a number of service settings. Aggression is the primary reason for people with ID to be admitted or re-admitted to institutional settings, and it is also the main reason for individuals in this client group to be prescribed behaviour-control drugs. Anger is a significant activator of aggression, but little is known about the emotional aspects of the lives of people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 42 publications
3
81
0
3
Order By: Relevance
“…37,[66][67][68][69] Similarly, comorbid substance abuse increases the risk of violence in patients with mental retardation. 70 Furthermore, violent mentally retarded adults have been shown to have larger brain ventricles than their non-violent counterparts, as well as a higher frequency of abnormal EEGs, yet no increased prevalence of seizure disorders (as for schizophrenia). 27,47,71,72 In addition to schizophrenia and mental retardation (with or without comorbidity), the personality disorders as independent primary diagnoses -in particular antisocial and other cluster B personality disorders -are associated with violent behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…37,[66][67][68][69] Similarly, comorbid substance abuse increases the risk of violence in patients with mental retardation. 70 Furthermore, violent mentally retarded adults have been shown to have larger brain ventricles than their non-violent counterparts, as well as a higher frequency of abnormal EEGs, yet no increased prevalence of seizure disorders (as for schizophrenia). 27,47,71,72 In addition to schizophrenia and mental retardation (with or without comorbidity), the personality disorders as independent primary diagnoses -in particular antisocial and other cluster B personality disorders -are associated with violent behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of waiting list controlled studies, Taylor et al (2002Taylor et al ( , 2004 have evaluated individual cognitive behavioural anger treatment with detained male patients who have mild-borderline ID and significant violent histories. Taylor et al (2002) reported a pilot study involving 20 detained male patients using an 18 session cognitive behavioural treatment comprising of six sessions of a psycho-educational and motivational preparatory phase, followed by a 12 session treatment phase based on individual formulation of each participant's anger problems and needs that followed the cognitive behavioural stages of cognitive preparation, skills acquisition, skills rehearsal and practice in vivo. Participant's self-report of anger intensity to provocation was significantly lower following the intervention in a treatment condition when compared with a waiting list control.…”
Section: Violence and Aggressionmentioning
confidence: 99%
“…Despite the consequences that anger and aggression problems have for people with DD directly, and for others around them, including direct care staff and systems concerned with their care and rehabilitation, there is little in the literature concerning the development of reliable and valid measures of these phenomena in this population (Novaco & Taylor, 2004;Taylor, 2002). Studies by Benson and Ivins (1992) and Rose and West (1999) have indicated that modified self-assessment measures of anger reactivity can have some limited reliability and validity with people with DD.…”
Section: Anger and Aggressionmentioning
confidence: 99%
“…This approach incorporates the stress inoculation paradigm (Meichenbaum, (2005) 1985) and has cognitive re-structuring, arousal reduction and behavioural skills training as its core components. Taylor (2002) and Taylor and Novaco (in press) have reviewed numerous case and case-series studies, and a small number of uncontrolled group studies involving individual and group therapy formats incorporating combinations of cognitive-behavioural techniques including selfmonitoring, relaxation and skills training that have yielded reductions in levels of anger and aggression that were maintained at follow-up. In addition there have now been three outcome trials that have established the effectiveness of group cognitive-behavioural anger treatment over waitlist controlled conditions with clients with DD and anger and aggression problems living in community settings (Lindsay et al, 2004a;Rose, West, & Clifford, 2000;Willner, Jones, Tams, & Green, 2002).…”
Section: Anger and Aggressionmentioning
confidence: 99%
See 1 more Smart Citation